THE INFLUENCE OF SOCIAL ACCESS AND ACCESS TO PUBLIC FACILITIES CHANGES IN CONSUMPTION PATTERNS - Mitra Musika Lubis; Darma Bakti; Rahmanta; Sri Fajar Ayu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The vast territory of Indonesia makes Indonesia rich in various foods. However, the irony is that the distribution of staple foods such as rice does not fully reach remote areas in Indonesia. This resulted in rice prices soaring and difficult to obtain. People don't care and try to switch to rice substitute foods such as bread, noodles, corn and other foods. This study aims to determine what factors influence the change in food habits from rice to non-rice. The research was conducted in Tanjung Pasir Village, Sei Merah Village, Lubuk Kertang Village, which is in Pangkalan Susu District, Langkat Regency, North Sumatra. The research model used is a descriptive quantitative research model. The data analysis used was Stuctural Equation Modeling (SEM) analysis assisted by AMOS 20.0 software. The data collection instrument used was a questionnaire instrument. The results of this study indicate that the factors of social access and public facilities influence changes in people's consumption patterns towards non-rice foods. The conclusion is that people in this area are experiencing diversification, changing consumption patterns to non-rice foods. The community prefers to look for food, especially for breakfast, to the stalls to look for non-rice foods such as bread, instant noodles, some corn and cassava. The reasons are: 1) The education factor can change people's food habits because it has an impact on the difficulty of getting a decent job, the quality of life is below standard, one of which is the difficulty to get rice; 2) The location of the market which is far away and difficult to access has resulted in soaring rice prices and this is one of the problems with public facilities; 3) The natural condition of the coast which lacks the availability of clean water and also poor sanitation makes it difficult for housewives to cook food at home.